2009
DOI: 10.1007/s00403-009-0994-y
|View full text |Cite
|
Sign up to set email alerts
|

The UV response of the skin: a review of the MAPK, NFκB and TNFα signal transduction pathways

Abstract: The sun emits different types of ultraviolet (UV) light. Our skin is a natural target of UV radiation which is involved in vitamin D3 production in our body. UV radiation at high doses is an environmental carcinogen which can elicit skin damage as well as inducing skin cancer. It can mediate inflammatory and immunological reactions through activation of receptors, DNA/RNA damage and production of reactive oxygen species. It is also involved in the release of pro-inflammatory cytokines, of which TNFalpha has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
194
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(206 citation statements)
references
References 106 publications
5
194
0
3
Order By: Relevance
“…MAPK-mediated signaling pathways are reportedly involved in UVB responses in keratinocytes (1). However, our data demonstrated that the target genes were less involved in MAPK-related signal transduction, suggesting that miRNA-based UVB protection pathways in keratinocytes may be mediated via anti-apoptosis and positive regulation of cell growth pathways, rather than through a MAPK pathway.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…MAPK-mediated signaling pathways are reportedly involved in UVB responses in keratinocytes (1). However, our data demonstrated that the target genes were less involved in MAPK-related signal transduction, suggesting that miRNA-based UVB protection pathways in keratinocytes may be mediated via anti-apoptosis and positive regulation of cell growth pathways, rather than through a MAPK pathway.…”
Section: Discussionmentioning
confidence: 58%
“…UV irradiation leads to cell aging, senescence, apoptosis and cancer in human keratinocytes by inducing reactive oxygen species (ROS), DNA damage and inflammatory and immunological reactions (1). Members of the mitogenactivated protein kinase (MAPK) family, including ERK1/2, p38 MAPK and JNK, are phosphorylated (activated) by UV irradiation (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UV radiation was also found to activate NF-κB signalling in an IKKindependent manner (Lewis and Spandau 2007) and promote the secretion of pro-inflammatory cytokines, such as IL-6 and TNF-α (Abeyama, Eng et al 2000, Grandjean-Laquerriere, Gangloff et al 2002. Interestingly, studies have linked altered pro-inflammatory signalling and cytokine release to UV-induced skin disorders, including SCC (Muthusamy and Piva 2010). UV-damage has also been shown to activate MAPK p38 and JNK signalling (described in Section 5.1) (Chouinard, Valerie et al 2002, Hildesheim, Awwad et al 2004, Schieke, Ruwiedel et al 2005, but whether the maintenance of proliferation, differentiation and homeostasis in the epidermis (Marcinkowska, Wiedlocha et al 1997, Mitev and Miteva 1999, Zhang, Pelech et al 2001, however, they also promote the growth of SCC (Tsang and Crowe 1999).…”
Section: Roles Of Irf6 In Trif-dependent Tlr Signalling In Keratinocymentioning
confidence: 99%
“…Crosstalk between these two transcription factors and signalling pathways exists and has been studied extensively (Zenz and Wagner 2006;Cooper and Bowden 2007). MAPK pathway is one of these pathways, which includes JNKs, ERKs and p38 MAP kinases (Assefa, Garmyn et al 1997;Muthusamy and Piva 2010). Other transcription factors characteristic of the UV response are JUNB, JUND, c-FOS, ETR101, EGR1, HRY and XBP-1 and E2F family of transcription factors (Li, Turi et al 2001;HazarRethinam, Endo-Munoz et al 2011;López-Camarillo, Aréchaga Ocampo et al 2011).…”
Section: Transcriptional Control Of Uv-induced Responsesmentioning
confidence: 99%